After religious education: lessons from continental pedagogy - Lewin, David (Journal of Religious Education, 2023)
This paper takes up the theme of divergent political and educational paths in Religious Education (RE) by drawing out some educational theories from the German tradition of what is sometimes called "continental pedagogy". As a development of work undertaken within the After Religious Education project, my interest in this paper is what these theories have to say about one aspect of education, namely the educational logic governing curricular presentation and representation. Within the German tradition, there is an established focus on "didactics" (the theory and practice of teaching) which informs the approach taken here. Rather than seeing RE as a particular corner of the curriculum with its own unique challenges, my main argument is that RE theory is part of wider educational landscape and therefore it could usefully engage more actively with the tradition of general didactics. The argument will present and contextualize the work of Wagenschein and Klafki, educational theorists who are not well known among Anglophone theorists of RE, but who offer insightful considerations of the holistic formation of the person to which RE can make a vital contribution.